Adaptive Model-Free Control And Localization For Single-Agent And Multi-Agent Nonlinear Dynamic Systems - Safaei, Ali (2019)
In this thesis, a unified solution comprising model-free control and localization algorithms is presented to address the tracking problem in single-agent completely unknown nonlinear dynamic systems, the formation-tracking problem in multi-agent completely unknown nonlinear dynamic system, and the cooperative localization problem for a team of mobile agents. The formulated model-free control algorithms, neither rely on the universal approximation characteristic of the artificial neural networks nor regressor-based approximation.